A Comprehensive Study on Digital Signature (International Journal of Innovative Research in Computer Science & Technology, 2021)
For secure and smart transactions over  open networks, the Digital Signature Concept is necessary.  It is having forms of programs with a view to make certain  the integrity of information exchanged or saved and to show  the identity of the originator to the recipient. Digital  Signature techniques are usually used in cryptographic  protocols to provide services like entity authentication,  authenticated key delivery and authenticated key  agreement. With using cellular devices as a client of  internet, the risk of unauthorized and unauthenticated get  admission to of crucial files (e.g. contracts, receipts, and so  forth.) is growing every day. Although Digital Signature is  supposed to be the solution for the unauthorized get right of  entry to, its implementation isn't always good enough till  now. The symmetric records transfer mechanism is used for  the transfer of essential documents, but there's a want of a  greater ready mechanism for safe transfer and verification  of the documents. This Research paper presents a  comprehensive study of Digital Signature and its benefits.
Keywords: Authentication; Cryptography; Digital Signature; Verification